Aged refuse as a medium to remediate leachate contaminated by heavy metals - Nik Daud, Nik Norsyahariati; Ismail, Farhana (DEStech Publications, 2015)
The performance of aged refuse (AR) as an alternative medium in a biofilter in order to treat leachate contaminated by heavy metals (i.e. Zinc, Iron, Cadmium, Lead and Copper) were assessed. The 8 years old age of refuse was used as a medium and leachate samples were collected at two different points at local municipal sanitary landfill. Results showed that more than 80% reduction of heavy metals for intermediate leachate whereas 30% and above reduction was assessed for young leachate with the highest reduction is 85% of Iron. It can be concluded that the AR biofilter are good enough for treating leachate contaminated by selected heavy metals especially for intermediate leachate.